Comparative analysis of positive thinking and stress levels in physicians and medical staff - V. V. Kozyreva; A. A. Cherniavskii (Вестник университета)
The article compares the features of positive thinking and stress levels in physicians and medical staff, but the nature of duties and work differs in many ways, which may serve to identify significant differences among workers of two similar professions. The purpose of the study is to examine the positive thinking and stress levels characteristics in helping professions. Objectives of the study are to analyze the scientific literature, to identify the positive thinking and stress levels in specialists, and to establish differences in these levels in specialists of different profiles. The subject of the study is the peculiarities of positive thinking and stress levels in specialists. The literature on the topic under study has been analyzed according to the works of N.E. Vodopyanova, T.O. Gordeeva, E.N. Osin, V.Y. Shevyakhova, and Yu.V. Scherbatykh. The following methods were used: stress manifestations complex assessment (Yu.V. Shcherbatykh (2008), questionnaire of successes and failures reaction ways for adults (STONE-V, T.O. Gordeeva, V.Y. Shevyakhova (2008), optimism and activity scale in N.E. Vodopyanova’s adaptation (2009). Statistically significant differences have been revealed only on the “Optimism in the situation of success” scale, which indicates the difference in the behavior of physicians and medical staff. The results of the study can be the basis for creating recommendations for helping employees cope with stress. The prospect is to extend the study of the phenomenon to other helping professions and compare the results.